Cultural Values and Alexithymia. (13th October 2014) - Lo, Chris
Alexithymia refers to difficulty with reflecting on and articulating emotional states. Previous research has found that Asian groups may tend toward greater alexithymia and that cultural values may mediate this difference, although the content of Asian values that form these pathways is unclear. This study examined the relationship between Confucian values, ethnicity, and alexithymia. A sample of 216 undergraduate students completed the Chinese Value Survey and the Toronto Alexithymia Scale. Asian Canadians scored more highly on alexithymia than non-Asian Canadians. Individuals who valued trustworthiness, patience, and kindness were found to be less alexithymic. The ability to be a source of kindness and security to others may be tied to the development of reflective awareness. Individuals who valued purity from desire and respect for social order were found to be more alexithymic. Such individuals may tend not to reflect on impure or socially disruptive thoughts and feelings. Values associated with purity and order mediated the difference between Asians and non-Asians on alexithymia. Asian Canadians may therefore score more highly on alexithymia because they prefer not to reflect on emotions associated with impurity or social disorder.